2020
DOI: 10.2174/1871526518666181001145041
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance and Effectiveness Against Respiratory Infections Among Hajj Pilgrims: A Systematic Review

Abstract: The role of hand hygiene in the prevention of respiratory tract infections in Hajj pilgrims has not been assessed through a focussed systematic review of the literature. Considering this, a systematic review was undertaken to synthesize the up-to-date literature on the compliance and effectiveness of hand hygiene among Hajj attendees. Major databases, including OVID Medline, were searched by using a combination of MeSH terms and text words for potentially relevant articles. Data from identified articles were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Hand washing with soap and water was the most common type of hand cleaning reportedly used by the study respondents in almost all the situations followed by alcohol hand rubbing. The results of this study are consistent with, and corroborate, the findings of other studies, including a systematic review, which found among Hajj pilgrims hand washing with soap was more popular than hand gel or sanitizers [18,21]. In contrast, a study explored domestic pilgrims' uptake of health preventive measures during the peak Hajj days found the proportion of respondents washing their hands with soap and cleaning hands with hand sanitizers was same (65%); however, pilgrims who were concerned about food poisoning were more likely to clean their hands with hand sanitizers (adjusted OR 2.5, 95% CI 1.1-5.4) indicating pilgrims' degree of concern may dictate the mode of hand hygiene [19].…”
Section: Discussionsupporting
confidence: 91%
“…Hand washing with soap and water was the most common type of hand cleaning reportedly used by the study respondents in almost all the situations followed by alcohol hand rubbing. The results of this study are consistent with, and corroborate, the findings of other studies, including a systematic review, which found among Hajj pilgrims hand washing with soap was more popular than hand gel or sanitizers [18,21]. In contrast, a study explored domestic pilgrims' uptake of health preventive measures during the peak Hajj days found the proportion of respondents washing their hands with soap and cleaning hands with hand sanitizers was same (65%); however, pilgrims who were concerned about food poisoning were more likely to clean their hands with hand sanitizers (adjusted OR 2.5, 95% CI 1.1-5.4) indicating pilgrims' degree of concern may dictate the mode of hand hygiene [19].…”
Section: Discussionsupporting
confidence: 91%
“…When participants were asked about their hand hygiene practices at specific high-risk situations, soap and water was the most preferred method reportedly used, followed by alcohol-based hand rubs. This finding is in parallel with the results of formerly conducted studies among attendees of Hajj and Umrah pilgrimage that found hand washing with soap and water was more prevalent than other hand hygiene methods [15,[26][27][28]. It is also noteworthy that Saudi Arabian citizens have a preference for using soap and water to ABHR as a preventive measure against COVID-19 [19].…”
Section: Practice Of Hand Hygienesupporting
confidence: 81%
“…Previous studies have not explored if demographic factors were associated with an intention to use non-pharmacological protective measures before travel and their actual use during Hajj. Nonetheless, earlier studies did conclude that health education prior to departure was significantly associated with greater compliance with preventative practices, particularly the use of facemasks and hand sanitizers [19][20][21][22].…”
Section: Discussionmentioning
confidence: 97%